Research on Control Mechanism of Surrounding Rock of Deep Gob-Side Entry Retaining - Jianxiong Liu; Jingke Wu; Yun Dong; Yanyan Gao; Jihua Zhang; Weizhong He; Jiarui Chen (Geofluids)
To address the large deformation of the surrounding rock of deep gob-side entry retaining under high stress, lithological characteristics of the surrounding rock and failure model of support body and their evolutionary processes are analyzed through field investigation and theoretical analysis. Failure mechanisms of surrounding rock and the technology to control it are studied systematically. The results show that the causes of the large deformation of the surrounding rock are weak thick mudstones with softening property and water absorption behavior, as well as its fragmentation, dilatancy, and long-term creep during strong disturbance and highly centralized stress states. The cross-section shape of the roadway after deformation and failure of the surrounding rock is obviously asymmetric in both the horizontal and vertical directions. Since the original system supporting the surrounding rock is unable to completely bear the load, each part of the supporting system is destroyed one after the other. The failure sequences of the surrounding rock are as follows: (1) roadway roof fracture in the filling area, (2) filling body fracture under eccentric load, (3) rapid subsidence of the roadway roof, and (4) external crack drum and rib spalling at the solid coal side. Due to this failure sequence, the entire surrounding rock becomes unstable. A partitioned coupling support and a quaternity control technology to support the surrounding rock are proposed, in which the roof of the filling area plays a key role. The technology can improve the overall stability of gob-side entry retaining, prevent support structure instability caused by local failure of the surrounding rock, and ensure the safety and smoothness of roadways.